Physicochemical Properties and Sensory Evaluation of Ready to Eat Tilapia in Tomato Sauces - Md Salleh, Nurhaziqah; Kormin, Faridah (Enhanced Knowledge in Sciences and Technology, 2025)
This study examines the qualities and consumer appeal of ready-to-eat tilapia in tomato sauces, prepared using retort processing. By focusing on tilapia, a widely farmed and versatile freshwater fish, this research introduces a fresh approach to creating convenient, nutritious, and long-lasting food products that cater to modern consumer needs. The retort processing method using fresh fish, carried out at 121°C for 40 minutes, ensures the product quality and ideal texture. Key aspects of the product, including texture, moisture content, viscosity, colour, and pH, were carefully analysed to understand how different formulations impact its physical and chemical properties. The sensory analysis test was conducted with 40 panellists using a 7-point hedonic scale to evaluate product characteristics such as appearance, aroma, texture, taste, and overall acceptance. Among the formulations tested were the control formulation, the formulation with food additives and seasonings, and the formulation without food additives and seasonings. The results of the nutritional analysis show that tilapia in retort bags has an energy content of 106 kilocalories (kcal) per 100 grams, including a high protein quantity (10.3 g) and a fat content (1.9 g). Relatively, this product also contains a high salt content of 487 mg per 100 grams, which should be considered with nutritional considerations. Overall, formulation 2 is the best formulation in this study and this study highlights the potential of retort technology to make tilapia more accessible and versatile in the food market. It also shows opportunities for improvements in formulation to increase production rates and enhance consumer satisfaction. With the production of innovative products and ready-to-eat products like this, this study aligns with current trends in producing quality food for today's lifestyle.